Abordagem da ergonomia para análise da acessibilidade a hóspedes com deficiência visual em hotéis: soluções de inclusão de pessoas cegas e com baixa visão - Santos, Larissa Nascimento dos (2012)
This study evaluates the level of accessibility for people with visual impairment (blindness and low vision) hotels in the city of Natal-RN, Brazil, and provides principles, guidelines and means of projective make hotels accessible, to promote comfort, autonomy and security of these people. We used a qualitative research methodology and quantitative trait descriptive, analytical and interpretive. Was taken as a base for field studies Ergonomic Analysis of Work, beginning with a study of the demands of accessibility of hotels and analyzing the modeling activity in these establishments through the application of interactional and observational techniques, such as film, photographic records, conversational actions and observation protocols. A protocol was developed and applied to evaluate the compliance of accessibility of hotels in the face of Brazilian technical standard NBR 9050 (2004). We used methods of Cognitive Task Analysis (CTA) associated with simulated activities to identify the processes of decision making and analyzing the observables of the activities performed by people with visual impairment (POS). Interviews were conducted with people who are blind and low vision in various cities in order to meet accessibility difficulties they faced in hotels and recommendations for improvement that they indicate. The mapping results showed that of 16 hotels 4 and 5 star studied in Natal-RN, reached only 7% of the 50 items of the protocol, while none of them reached 70% of the items. About the results obtained in simulated activities and analyzed from the ATC, we saw that the hotel where it was performed this step shows a need to adequately address the guests with visual impairments